The Influence of the Effectiveness of Accounting Learning Process on Students’ Learning Achievements - Natalina Premastuti Brataningrum; Laurentius Saptono (LPMPP Universitas Negeri Yogyakarta, 2017)
This study was aimed to figure out the influence of effectiveness degree of learning process on basic competences of accounting cycles at service companies on students’ learning achievements using mediating effects of self-efficacy and students’ learning motivation variables. This was exploratory research which was conducted from February to May 2017. The research population was class XII social students in Sleman Regency, Special Region of Yogyakarta who had learned basic competences to practice accounting cycles at service companies based on 2013 Curriculum at the academic year of 2016/2017. The research samples were 238 students selected using stratified random sampling technique. Data gathering techniques employed questionnaires and documentations. The data then were analyzed using descriptive statistics and Partial Least Squares SEM. The results of the research revealed that: 1) the effectiveness degree of accounting learning process had positive influence on students’ learning motivation; 2) the effectiveness degree of accounting learning process had positive and significant influence on students’ self-efficacy; 3) the effectiveness degree of accounting learning process had positive and significant influence on students’ learning achievements; 4) learning motivation had positive and significant influence on students’ learning achievements; 5) self-efficacy had positive and significant influence on students’ learning motivation; 6) self-efficacy had positive and significant influence on students’ learning achievements.